Secukinumab demonstrated sustained retention, effectiveness and safety in a real‐world setting in patients with moderate‐to‐severe plaque psoriasis: long‐term results from an interim analysis of the SERENA study. (4th July 2022) - Augustin, M.; Sator, P.G.; von Kiedrowski, R.; Conrad, C.; Rigopoulos, D.; Romanelli, M.; Ghislain, P.‐D.; Torres, T.; Ioannides, D.; Aassi, M.; Schulz, B.; Jagiello, P.; et al.
Abstract: Background: Randomized controlled trials of secukinumab have shown sustained efficacy and a favourable safety profile in multiple manifestations of psoriatic disease. Objectives: To assess the long‐term, real‐world retention, effectiveness and safety of secukinumab in routine clinical practice for the treatment of moderate‐to‐severe plaque‐type psoriasis (PsO). Methods: SERENA (CAIN457A3403) is a large, ongoing, longitudinal, observational study conducted at 438 sites and 19 countries for an expected duration of up to 5 years in adult patients with moderate‐to‐severe PsO, psoriatic arthritis and ankylosing spondylitis. Patients received ≥16 weeks of secukinumab treatment before enrolment. This interim analysis presents data from PsO patients, who were enrolled in the study between October‐2016 and October‐2018 and were observed for ≥2 years. Results: In total, 1756 patients (67.3% male) with a mean age of 48.4 years and body mass index of 28.8 kg/m 2 were included in the analysis. The secukinumab treatment retention rates after 1, 2 and 3 years in the study were 88.0%, 76.4% and 60.5%, respectively. Of the 648 patients who discontinued the study, the most common reasons included lack of efficacy (42.6%), adverse event (17.4%), physician decision (12.2%) and subject decision (11.6%). Mean ± SD absolute PASI was 21.0 ± 13.0 at the start of treatment ( n = 1, 564). At baseline, the mean ± SD PASI score reduced to 2.6 ± 4.8 and remained low at Year 1 (2.3 ± 4.3), Year 2 (1.9 ± 3.6) and Year 3 (1.9 ± 3.5). The safety profile of secukinumab during the SERENA study was consistent with its known safety profile, with no new safety signals reported. Particularly, low rates of inflammatory bowel disease (0.3%; Incidence Rate [IR]:0.15), candida infections (3.1%; IR:1.43) and MACE (0.9%; IR:0.37) were observed. Conclusions: Secukinumab showed high treatment persistence, sustained effectiveness and a favourable safety profile up to 3 years of follow‐up in the real‐world population of PsO patients observed in SERENA.